Gold nanoparticles on OMS-2 for heterogeneously catalyzed aerobic oxidative α, β-dehydrogenation of β-heteroatom-substituted ketones. Issue 99 (25th November 2016) - Yoshii, Daichi; Jin, Xiongjie; Yatabe, Takafumi; Hasegawa, Jun-ya; Yamaguchi, Kazuya; Mizuno, Noritaka
Abstract : In the presence of Au/OMS-2, various kinds of β-heteroatom-substituted α, β-unsaturated ketones can be synthesized through aerobic oxidative dehydrogenation of the corresponding saturated ketones. Abstract : In the presence of Au nanoparticles supported on manganese oxide OMS-2 (Au/OMS-2), various kinds of β-heteroatom-substituted α, β-unsaturated ketones (heteroatom = N, O, S) can be synthesized through α, β-dehydrogenation of the corresponding saturated ketones using O2 (in air) as the oxidant. The catalysis of Au/OMS-2 is truly heterogeneous, and the catalyst can be reused.